On a regularized Levenberg–Marquardt method for solving nonlinear inverse problems - Jin, Qinian (Numerische Mathematik, 2010)
We consider a regularized Levenberg–Marquardt method for solving nonlinear ill-posed inverse problems. We use the discrepancy principle to terminate the iteration. Under certain conditions, we prove the convergence of the method and obtain the order optimal convergence rates when the exact solution satisfies suitable source-wise representations.